Quality appraisal of clinical practice guidelines for attention deficit hyperactivity disorder: a systematic review using the appraisal of guidelines for research and evaluation (AGREE II) instrument - Wahyu, Muhammad Dwi; Sugimoto, Atsunori; Zain, Ekachaeryanti; Parawansa, Faisal Budisasmita Paturungi; Kasahara, Hiroyuki; Yoshinaga, Kiyohiro; Egawa, Jun (Frontiers in Psychiatry, 2025)
ObjectivesAttention deficit hyperactivity disorder (ADHD) can significantly impact multiple life conditions across the lifespan. Reliable clinical practice guidelines (CPGs) are crucial for the clinical decision-making for the diagnosis and management of ADHD. This study aimed to assess the quality of current CPGs for the diagnosis and management of ADHD.MethodsWe conducted a systematic literature search within Pubmed, Google Scholar, the Agency for Healthcare Research and Quality, Dynamed, the National Institute for Health and Care Excellence (NICE), the National Health and Medical Research Council (NHMRC), and other local and online databases started January 19, 2022. We assessed the guideline quality using the Appraisal of Guidelines for Research and Evaluation (AGREE II) instrument. All of the included guidelines were critically appraised by five independent reviewers. We also evaluated the interrater reliability of each AGREE II domain and the overall domain score by calculating the intraclass correlation coefficient (ICC) using IBM SPSS Statistics version 28.ResultsA total of 11 CPGs were included in the study. The majority of the CPGs achieved the highest score in domain 4 “Clarity of Presentation” (mean ± standard deviation, 73.73% ± 12.5%). The domains that achieved the lowest scores were domains 5 “Applicability” (mean ± standard deviation, 45.18% ± 16.4%) and 3 “Rigor of Development” (mean ± standard deviation, 51.09% ± 24.1%). The American Academy of Pediatrics (AAP), NICE, and the Malaysian Health Technology Assessment Section (MAHTAS) CPGs were identified as the strongly recommended guidelines. All AGREE II domains yielded varied interrater reliability results; the full domain ICC ranged from 0.265 (95% confidence interval, −0.470 to 0.665) to 0.758 (95% confidence interval, 0.515 to 0.889).ConclusionsOur appraisal indicated that the quality of current ADHD guidelines is varied, and three CPGs were classified as strongly recommended. Our findings offer relevant healthcare providers valuable insight into the appropriate selection of ADHD guidelines in clinical practice.Systematic review registrationhttps://inplasy.com/inplasy-2022-8-0001/, identifier INPLASY202280001